Zeugizō: The Language of Marital Infidelity in the Account of Treachery Toward the Ancestral Laws in 1 Macc 1:15 - Nawrot, Janusz (Verbum Vitae, 2020)
The present article deals with a linguistic issue well known in the Bible but not usually overtly present in the terminology of Hebrew and Greek Scripture. It concerns the sexual sphere of human life and is expressed by the verb zeugizō (1 Macc 1:15). This term appears only once in the Septuagint and is not featured in any of the other inspired books. However, the discovery of a non-biblical text which includes the term in question, as well as the inclusion of the verb by the Jewish authors of the Greek Bible from the 2nd century AD, shed important light on the sense of the verb in the First Book of the Maccabees. The exegesis carried out reveals just how harsh was the hagiographer’s critique of, and judgment upon, the supporters of the Hellenization of Judea.